Polymer‐Stabilized Percolation Membranes Based on Nanosized Zeolitic Imidazolate Frameworks for H2/CO2 Separation. Issue 7 (22nd May 2018) - Sánchez‐Laínez, Javier; Friebe, Sebastian; Zornoza, Beatriz; Mundstock, Alexander; Strauß, Ina; Téllez, Carlos; Caro, Jürgen; Coronas, Joaquín
Abstract: This work shows the preparation of self‐supported composite membranes prepared with the nano‐sized zeolitic imidazolate frameworks (ZIFs): ZIF‐8, ZIF‐7(III) and ZIF‐7/8 core‐shells. The membranes consist of compressed pellets of ZIF nanoparticles (up to 74 wt% loading) stabilized with gas‐impermeable epoxy resin, providing a gas transport‐selective percolation network named polymer‐stabilized percolation membrane (PSPM). The different PSPMs have been characterized by SEM, TGA, XRD, FTIR and Raman. FIB/SEM has provided a 3D reconstruction of the composite thanks to the slice and view technique, allowing a perfect visualization of the inside of the network. The N2 adsorption properties have also been studied and compared with those of ZIFs in powder state. The gas separation performance of these membranes has been tested for the H2 /CO2 mixture. The PSPMs were tested with feed pressures up to 5 bar, obtaining H2 permeabilities of hundreds of Barrer and a maximum H2 /CO2 selectivity of 12.3. Abstract : Polymer‐stabilized percolation membranes have been prepared with nanoparticles of ZIF‐8, ZIF‐7(III) and ZIF‐7/8 core‐shells. These membranes show a high H2 /CO2 separation performance, with H2 permeabilities over 100 Barrer and a maximum H2 /CO2 selectivity of 12.3.